Tryptophan at the transmembrane–cytosolic junction modulates thrombopoietin receptor dimerization and activation - Jean‐Philippe Defour; Miki Itaya; Vitalina Gryshkova; Ian Brett; C. Pecquet; Takeshi Sato; Steven O. Smith; Stefan N. Constantinescu (2013)
Dimerization of single-pass membrane receptors is essential for activation. In the human thrombopoietin receptor (TpoR), a unique amphipathic RWQFP motif separates the transmembrane (TM) and intracellular domains. Using a combination of mutagenesis, spectroscopy, and biochemical assays, we show that W515 of this motif impairs dimerization of the upstream TpoR TM helix. TpoR is unusual in that a specific residue is required for this inhibitory function, which prevents receptor self-activation. Mutations as diverse as W515K and W515L cause oncogenic activation of TpoR and lead to human myeloproliferative neoplasms. Two lines of evidence support a general mechanism in which W515 at the intracellular juxtamembrane boundary inhibits dimerization of the TpoR TM helix by increasing the helix tilt angle relative to the membrane bilayer normal, which prevents the formation of stabilizing TM dimer contacts. First, measurements using polarized infrared spectroscopy show that the isolated TM domain of the active W515K mutant has a helix tilt angle closer to the bilayer normal than that of the wild-type receptor. Second, we identify second-site R514W and Q516W mutations that reverse dimerization and tilt angle changes induced by the W515K and W515L mutations. The second-site mutations prevent constitutive activation of TpoR W515K/L, while preserving ligand-induced signaling. The ability of tryptophan to influence the angle and dimerization of the TM helix in wild-type TpoR and in the second-site revertants is likely associated with its strong preference to be buried in the headgroup region of membrane bilayers.